2022
DOI: 10.3390/biomedicines10112839
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence for Early Detection of Chest Nodules in X-ray Images

Abstract: Early detection increases overall survival among patients with lung cancer. This study formulated a machine learning method that processes chest X-rays (CXRs) to detect lung cancer early. After we preprocessed our dataset using monochrome and brightness correction, we used different kinds of preprocessing methods to enhance image contrast and then used U-net to perform lung segmentation. We used 559 CXRs with a single lung nodule labeled by experts to train a You Only Look Once version 4 (YOLOv4) deep-learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…To date, only a few studies have demonstrated the performance of deep learning algorithms in detecting and segmenting pulmonary nodule. Chiu et al 29 developed a deep learning model based on the You Only Look Once version 4 for detecting pulmonary nodules. They demonstrated that an AI model with a combination of preprocessing approaches achieved the highest sensitivity of 79%, with 3.04 false positives per image, indicating a low positive predictive value.…”
Section: Assessing Current Literaturementioning
confidence: 99%
“…To date, only a few studies have demonstrated the performance of deep learning algorithms in detecting and segmenting pulmonary nodule. Chiu et al 29 developed a deep learning model based on the You Only Look Once version 4 for detecting pulmonary nodules. They demonstrated that an AI model with a combination of preprocessing approaches achieved the highest sensitivity of 79%, with 3.04 false positives per image, indicating a low positive predictive value.…”
Section: Assessing Current Literaturementioning
confidence: 99%
“…With the development of image segmentation, more and more researchers are committed to using image segmentation in the field of medical images to assist in the diagnosis of some critical diseases including liver cancer [ 8 ], lung cancer [ 9 ], prostate cancer [ 10 ], and some kidney diseases [ 11 ]. Ronneberger et al, 2015 [ 12 ] borrowed the ideas of FCN and then proposed an end-to-end “U-shaped” network, U-Net, for medical image segmentation.…”
Section: Related Workmentioning
confidence: 99%
“…With the development of image segmentation, more and more researchers are committed to using image segmentation in the field of medical images to assist in the diagnosis of some critical diseases including liver cancer [8], lung cancer [9], prostate cancer [10], This paper proposes three modules, the S-conv Blocks, the Multi-scale Dilated Convolution Modules (MDC), and the Multi-scale Feature Fusion Modules (MFF). These modules are plug-and-play, and many ablation results show that each module improves the segmentation accuracy of the network compared to CA-Net, which is of great significance for the practical clinical application of melanoma segmentation.…”
Section: Image Segmentationmentioning
confidence: 99%
“…Therefore, the development of CAD systems to support pulmonologists and radiologists in the assessment of chest radiographs is a priority in the respiratory community. As a core part of these systems, the task of segmenting the lung fields is critical to enable the automatic delivery of precise information about the anatomical structures identifiable in CXR images (e.g., quantification of lung nodules [18,19], detection of lung disease [20], [21] or heart failure [22]).…”
Section: Introductionmentioning
confidence: 99%